Challenging racism through schools: teacher attitudes to cultural diversity and multicultural education in Sydney, Australia. Issue 3 (3rd May 2016) - Forrest, James; Lean, Garth; Dunn, Kevin
Abstract : How school teachers act to challenge racism in schools is a vital concern in an immigrant society like Australia. A 10% response from a self-administered online survey of government (public) primary and secondary school teachers across Sydney, Australia's largest EthniCity, examines attitudes of classroom teachers towards cultural diversity, goals of multicultural education, and strategies to implement anti-racist strategies. Principal components analysis (PCA) of attitudes tease out the varied influence of opinion on multicultural education, diversity, and anti-racism. Classroom teachers are overwhelmingly supportive of cultural diversity, multicultural education and strategies to combat racism and discrimination, and these views hardly vary across the different geographic zones of the city, unlike attitudes within the general community. However, teacher knowledge about the implementation of multicultural policy does vary, and is positively associated with the extent of population diversity and socio-economic status (SES) of the communities surrounding the schools.